Micro Infrastructure : Regulators Must Take Small Operators Seriously - Baker, Bill (World Bank, Washington, DC, 2012)
Small-scale providers of infrastructure services, are proving to be more responsive than utilities, to needs of poor consumers. They might be delivering water services by tanker, transport services by minivan, or electricity through mini-grids, or household solar panels. They make their services affordable to the poor, by using cheaper technology, or permitting flexible payment. Regulators are customarily hostile to these alternative providers. The note thus suggests that the interests of the poor, would be better served if regulators treated them as valid service providers, and brought them under a regulatory umbrella.